Análisis comparativo de diferentes esquemas de suficiencia en generación eléctrica: Algunas reflexiones para el mercado eléctrico en Colombia (2016)
The Colombian electricity market has been facing difficulties with the occurrence of El Niño 2015-2016 that showed flaws in the market design. This paper makes an international referencing of different types of electricity market designs focused mainly on the mechanisms used to ensure generation capacity adequacy, describes the current problems and makes some recommendations for the Colombian electricity market based on the advantages, disadvantages and adaptability evidenced in the analyzed markets of Nord Pool, Alberta, PJM, Chile, Brazil and Panama.